The relationship of Biorhythm in its four cycles with the results of the volleyball transmissions among the participants in the 2019 Golden Square championship - Farhood, Nidaa Yasir; Nasser, Prof. Dr. Abdul Jalil Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the relationship of Biorhythm with its four sessions (physical, emotional, mental and intuitive) to the level of transmission in volleyball in terms of the transmission being unsuccessful or successful and also if the transmission is positive influencing or negative is not affecting as well as the possibility of achieving the direct point Ace. The research sample consisted of 8 players .They represents the teams participating in the Iraqi Golden Square Championship. The results showed that there is no statistically significant correlation between the cycles of Biorhythm and the level of transmission according to the mentioned variables, as the researchers stressed that there is a great exaggeration in the level of the impact of Biorhythm at the technical level of athletes, as well as their assurance that the changes What happens as a result of Biorhythm cycles is not the level that leads to a change in technical performance or a change in the results of matches.